Effect of jogging and low calorie diet on body weight loss and fat percentage among overweight women - Zahari, Siti Norishah (2018)
Malaysia has growing health problem and increase rate of community with chronic diseases which relate to overweight due to lifestyle changes such as decrease physical activity, increase sedentary behaviour and unhealthy eating habits. This study aims to compare between the effects of exercise alone and diet alone on body weight loss and fat percentage among overweight women. A total of ten sedentary and overweight women (N = 10) were recruited in this study and were randomly assigned into either exercise group (n = 6) or diet group (n = 4). During the four weeks of the intervention period, participants in the exercise group performed jogging five times per week (30 min per session) at 60-80% of maximum heart rate (HRmax) intensity while participants in the diet group consumed low calorie diet throughout the 4 weeks of the study duration. The measurements of body weight and body fat percentage of all the participants were measured before and after the intervention period. As a result, it was found that there was no significant difference (p > 0.05) on body weight loss between groups after the 4 weeks of intervention period. However, body weight loss was greater in the exercise group compared to the diet group. There was a significant decrement (p = 0.008) of body fat percentage in the exercise group after the 4 weeks of the intervention period but not (p = 0.361) in the diet group. As a conclusion, this study found that diet is more effective inreducing body weight while exercise is a more effective way to shed excessive body fat.